SAVE THE Sea Turtles - Musgrave, Ruth A.; Smith, Grace Hill; Romero, Libby; Weglinski, Michaela (London : Dorling Kindersley Limited, 2023)
Swim along with the seven kinds of sea turtles as they glide and dive in the sea. Find out how you can help these animals stay safe.
Includes questions and exercises
Keywords: Sea turtles -- Juvenile literature; Readers (Pre-level)